Predictors of Childcare Task Division and Shared Parenting Attitudes in Families with Youthful Children in Turkey - Erci, Behice (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: The division of child-care tasks is a critical element of the family system that has already received considerable attention from researchers and practitioners. The psychological and relational dynamics involved in coping together and sharing in their roles as parents with young children are at the forefront of this study. The purpose of this research was to determine the predictors of child-care task division and shared parenting attitudes in families with youthful children. Methods: This study was utilized in a cross-sectional design. The study population has consisted of couples with at least one child three years or younger. The couples were selected by a random sampling method. Data were collected using the Child Care Tasks and Shared Parenting Attitudes in Families Scale and an additional form for demographic characteristics of participants. The CCTS was designed to measure what percentages of times specific child-care tasks are completed by the mother alone, the father alone, and parents together. Respondents were asked to estimate the percentages for each task jointly. The alpha coefficient for the total CCT was 0.74. A total of 177 parent couples self-completed the instruments. This procedure took approximately 20–30 min for each study participant. Predictor variables of the study were mother’s age, father’s age, mother’s education level, father’s education level, mother’s occupation, father’s occupation, monthly income, number of children, age of the youngest child, and gender of the youngest child. Pearson’s correlation, factor, and reliability analyses, paired t-tests, multiple regression analyses were used CCT. Results: Mothers in this study spent a significantly more significant proportion of their time completing independently child-care tasks more time alone than fathers. Considering all child-care tasks together, the average percentages of time that couples’ estimated mothers spent on child-care tasks were between 40 and 60%, fathers’ average percentages were 20 to 40%, and parents worked together approximately 20 to 40% in completing the tasks. Parenting goals of employee mothers were similar to their partners. Also, employed mothers were flexible with their partners regarding the division of child care. Conclusions: Demographic variables of the couples and their child were significant predictors for CCT and shared parenting attitudes in families. It is possible that mothers who tend to share this responsibility feel a greater sense of commitment to their families.